2019
DOI: 10.1038/s41598-019-44201-7
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary upregulation of heart rate variability through biofeedback is improved by mental contemplative training

Abstract: Regulation of the parasympathetic nervous system, indexed through high frequency heart rate variability (HF-HRV), is indicative of physical and psychological health. However, little is known about the trainability of this capacity. We investigated the effects of a 9-month mental training program (the ReSource Project; n = 298) on voluntary HF-HRV upregulation, assessed with a novel biofeedback procedure. The program consisted of attentional, interoceptive, socio-affective and socio-cognitive training elements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“… 20 Furthermore, intentionally strengthening feeling safe may provide a basis for voluntary upregulation of HRV and self-regulation of autonomic function. 72 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Furthermore, intentionally strengthening feeling safe may provide a basis for voluntary upregulation of HRV and self-regulation of autonomic function. 72 …”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal randomized controlled trials are needed to evaluate the sustainability of changes in autonomic nervous system and HPA-axis activity and immune function. 72 A better understanding of potential moderating variables, including comorbid conditions such as hypertension and diabetes, will be important to research efforts. 59 Perceived stress, sensitivity to social disconnection, anxiety and depression symptoms, and sleep disturbance may also serve as relevant moderators.…”
Section: Discussionmentioning
confidence: 99%
“…Initial assessment of mental health at point of hire for ICU nurses and ongoing assessment checks can assist in early identification and prevention of PTSD. HRV can be a valuable, noninvasive measure in detection of psychological stress and assessment of the autonomic nervous system (Bornemann et al, 2019; Hourani et al, 2020). If low HRV is discerned at point of hire, nurse managers could suggest mindfulness-based cognitive training (MBCT) to mitigate psychological stress.…”
Section: Implications For Occupational Health Nursingmentioning
confidence: 99%
“…It should be noted that afferent signaling changes should not be the only mechanism to drive plastic changes in autonomic circuitry. Bornemann et al (2019) recently showed that a long-lasting mental training intervention influenced the parasympathetic modulation of heart rate variability in individuals carrying the homozygous allele AA of the oxytocin receptor gene. It remains to be determined whether this or other stimuli do change the plasticity of preautonomic OTergic pathways.…”
Section: Sham-smentioning
confidence: 99%